2018
DOI: 10.1038/s41467-017-02720-9
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel-like factor 4-dependent Staufen1-mediated mRNA decay regulates cortical neurogenesis

Abstract: Kruppel-like factor 4 (Klf4) is a zinc-finger-containing protein that plays a critical role in diverse cellular physiology. While most of these functions attribute to its role as a transcription factor, it is postulated that Klf4 may play a role other than transcriptional regulation. Here we demonstrate that Klf4 loss in neural progenitor cells (NPCs) leads to increased neurogenesis and reduced self-renewal in mice. In addition, Klf4 interacts with RNA-binding protein Staufen1 (Stau1) and RNA helicase Ddx5/17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…The isolated spiral ganglion cells were cultured in N2 medium containing basic fibroblast growth factor (bFGF; 20 ng/mL, PeproTech, Rocky Hill, NJ, USA) for 4 days to maintain stem cell characteristics and then evaluated for Nestin and Sox2 expression. To induce differentiation, the cells were seeded and further cultured in bFGF depleted medium [ 11 - 13 ]. Neurosphere culturing was conducted as has been described previously [ 11 - 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The isolated spiral ganglion cells were cultured in N2 medium containing basic fibroblast growth factor (bFGF; 20 ng/mL, PeproTech, Rocky Hill, NJ, USA) for 4 days to maintain stem cell characteristics and then evaluated for Nestin and Sox2 expression. To induce differentiation, the cells were seeded and further cultured in bFGF depleted medium [ 11 - 13 ]. Neurosphere culturing was conducted as has been described previously [ 11 - 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…To induce differentiation, the cells were seeded and further cultured in bFGF depleted medium [ 11 - 13 ]. Neurosphere culturing was conducted as has been described previously [ 11 - 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a chronic metabolic disease caused by the interaction of genetic and environmental factors [1,24]. A large number of studies have shown that STAU1 can regulate cell growth and nerve differentiation [25]. However, little is known about the post-transcriptional regulation of adipogenesis by STAU1.…”
Section: Discussionmentioning
confidence: 99%
“…Dusp1 has been implicated in neuroprotection [41,42] and has been linked with diabetes related cognitive impairment [43] . Klf4 is involved in neurite growth and regeneration in hippocampal and cortical neurons, and its dysregulation has been linked to various neurological disorders [44,45] .…”
Section: Discussionmentioning
confidence: 99%